The effect of testing procedure on DSC measurements of Gd-Ti-Zr alloy using ZrO2 container - Turalska, Patrycja; Homa, Marta; Sobczak, Natalia; Gazda, Andrzej; Wierzbicka-Miernik, Anna; Kaban, Ivan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Differential Scanning Calorimetry (DSC) was applied in order to determine the critical temperatures phase transformations of the Gd40Ti30Zr30 alloy (wt%). The comparative measurements were carried out by means of three types of measuring devices at a temperature up to 1650°C, in the same flow gas atmosphere (Ar, 99.9992%) using different testing procedures allowing to get dissimilar oxygen contents in the surrounding atmosphere. The high temperature interaction and reactivity taking place between molten alloy samples and ZrO2 container during DSC tests were evaluated by structural analysis of the resulting interfaces using the alloy samples solidified inside ZrO2 containers. The conducted research has demonstrated methodological difficulties with testing Gd-rich alloys by the container-assisted DSC method. The results of structural characterization confirmed the reaction between the liquid Gd40Ti30Zr30 alloy and the container material occurring in flowing argon atmosphere with significantly reduced oxygen content.